2008
DOI: 10.1038/sj.bjc.6604546
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil factor 3: a novel serum marker identified by gene expression profiling in high-grade endometrial carcinomas

Abstract: This study identifies the genetic fingerprint of poorly differentiated endometrioid endometrial carcinomas (G3-EEC) and analyses the potential utility of trefoil factor 3 (TFF3) as novel serum marker in G3-EEC. Affymetrix microarrays were used to identify the gene expression patterns of 19 snap-frozen G3-EEC and 15 normal endometrium (NE) biopsies. Quantitative real-time PCR (qRT-PCR) and immunohistochemistry were used to validate TFF3 expression. Finally, TFF3 serum levels were determined by ELISA in 25 G3-EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Interestingly, recent studies demonstrated that serum TFF3 levels were increased in patients with high-grade endometrial cancer [18], and in patients with advanced prostate cancer [19], and TFF3 was overexpressed in the tissues of these cancers [18,20]. Further studies are required to elucidate the mechanism of the linkage between TFF3 and gastric cancer or other types of cancers.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, recent studies demonstrated that serum TFF3 levels were increased in patients with high-grade endometrial cancer [18], and in patients with advanced prostate cancer [19], and TFF3 was overexpressed in the tissues of these cancers [18,20]. Further studies are required to elucidate the mechanism of the linkage between TFF3 and gastric cancer or other types of cancers.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, serum TFF3 levels in lung, pancreatic, endometrial and advanced prostate cancer patients are up-regulated significantly [42,75,95,96]. Therefore, increased serum TFF3 levels may not be specific for GC.…”
Section: Upregulation Of the Serum Concentrations Of Tffs In Gcmentioning
confidence: 90%
“…Several studies have reported that serum levels of TFF are significantly increased in patients with cancer (mainly gastric cancer) and thus serve as a potential biomarker for cancer screening. [13][14][15][16] Therefore, we conducted this study to determine the serum levels of TFF3 in patients with CRC and assess the diagnostic accuracy of serum TFF3. The diagnostic accuracy was further analyzed in comparison with the serum CEA level.…”
Section: Introductionmentioning
confidence: 99%